2006
DOI: 10.1359/jbmr.060212
|View full text |Cite
|
Sign up to set email alerts
|

Full Length or Fragments in Hormone Studies?

Abstract: We fully agree with Dr Martin that our study has specifically addressed the role of amino terminal fragments of PTH-related protein (PTHrP) and PTH in osteoblast differentiation. The effects of both fragments are mediated by the PTH/PTHrP type 1 receptor (PTHR1), and in concordance with extensive data, we did not observe a difference in effect of both hormone fragments. With respect to the role of PTHrP in osteoblast differentiation, many questions are still unresolved.First, PTHrP is a prepro-hormone subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Recently, Hu et al reported that Piezo1 activation promotes osteogenic differentiation of Gli1 + MSCs by activating the Wnt/β-catenin signaling pathway (HU et al, 2023). Moreover, TGF-β/BMP signal and Hh signal have been confirmed to have a synergistic effect on the osteogenic differentiation of MSCs, activation of both increases osteogenic potential of MSCs ( VAN DER HORST et al, 2003;REICHERT et al, 2013). The relationship between the Hh and Wnt signaling pathways is particularly complex.…”
Section: Interplay Of Signaling Pathways In Jaw Defect Repairmentioning
confidence: 99%
“…Recently, Hu et al reported that Piezo1 activation promotes osteogenic differentiation of Gli1 + MSCs by activating the Wnt/β-catenin signaling pathway (HU et al, 2023). Moreover, TGF-β/BMP signal and Hh signal have been confirmed to have a synergistic effect on the osteogenic differentiation of MSCs, activation of both increases osteogenic potential of MSCs ( VAN DER HORST et al, 2003;REICHERT et al, 2013). The relationship between the Hh and Wnt signaling pathways is particularly complex.…”
Section: Interplay Of Signaling Pathways In Jaw Defect Repairmentioning
confidence: 99%